Leber Hereditary Optic Neuropathy: Report of Two Cases and Literature Overview - Duc Anh, Nguyen; Thanh Tung, Hoang; Thi Hong Nhung, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 3, 2024)
Introduction: Leber hereditary optic neuropathy (LHON) is a rare genetic condition characterized by bilateral irreversible vision loss, predominantly affecting young males. Case presentation: We report two clinical cases of two young male patients who were admitted to the hospital because of painless vision loss. Their family members either have the LHON condition or carry a mutation of that in their gene. Funduscopic examination of the optic nerve currently appeared to have temporal pallor. Orbital Magnetic Resonance Imaging (MRI) scan showed hyperintensity of the optic nerve. Optical Coherence Tomography (OCT) of the optic nerve head and retinal nerve fiber layer showed thinning of the temporal nerve fiber layer. Humphrey's visual field revealed paracentral scotoma. Genetic testing revealed the patients had a m.11778G > A mutation in the MT-ND4 gene. They were both treated with oral Coenzyme Q10 and Idebenone. Conclusions: Leber's hereditary optic neuropathy may mimic optic neuritis in the acute phase, requiring precise, systematic clinical evaluation and genetic testing for confirmation.